Reformed child and adolescent mental health services in a devolved healthcare system: a mixed-methods case study of an implementation site - Banwell, Emily; Humphrey, Neil; Qualter, Pamela (Frontiers in Health Services, 2023)
Background Efforts are being made to reform and reconceptualise children and young people's (CYP) mental health services. This is in response to a rapid increase in mental health difficulties in this population, and the shortcomings of current service provision. The present study seeks to comprehensively evaluate the local implementation of the THRIVE Framework for System Change in Greater Manchester, UK (GM i-THRIVE) from 2018 to 2021. The framework was designed to change the way mental health is perceived, and subsequently how support is allocated. The current study focusses on the implementation of the framework's principles into CYP mental health support in the region. Methods The study comprised three methodological components, beginning with examination of the GM i-THRIVE implementation plan and self-assessment questionnaire measure using the Quality Implementation Tool. This was to provide a wider backdrop of implementation method adequacy to the rest of the study's findings. Subsequently, evaluation measures completed by professionals across Greater Manchester were examined to establish implementation progress, before corroborating key items from this measure with thematically analysed interview data from six CYP (13–22 years) who recently received mental health support in the region. Levels of agreement between staff and CYP were examined. Results GM i-THRIVE's implementation plan and self-assessment measure were respectively deemed a strong guiding foundation, and a suitable way of evaluating implementation progress. Every principle within the self-assessment measure demonstrated closer alignment with the THRIVE Framework as time progressed. Two themes were developed from the qualitative interview data, each overarching four subthemes: (1) Qualities of the service: information and decision sharing; communication and continuity; needs-based support; compassion and trust, and (2) The mental health journey: beginnings; endings; waiting; satisfaction with support. A good level of agreement between CYP testimony and staff progress reports was found. Conclusions Findings suggested that the experiences of the CYP in the sample, who were interviewed in the spring to summer period of 2022, were overwhelmingly positive. The rich insights into mental health support offered by the young participants lead us to recommend continued qualitative research with service-users as GM i-THRIVE's embedding period continues, with focus on representing a wide range of experiences in future research samples. Methodological limitations were explored, including the extent to which true cross-references could be made between professional and CYP accounts.